Complications of Alloplast Rhinoplasty and Their Management: A Comprehensive Review - Choi, Ji Yun (Facial Plastic Surgery, 2020)
In Asian countries, augmentation rhinoplasty is especially common, where alloplastic implants are used much more commonly than autologous tissues. In rhinoplasty, such artificial materials include silicone, expanded polytetrafluoroethylene (ePTFE), porous high-density polyethylene (pHDPE), and acellular human dermis. As the use of implants has become increasingly common in rhinoplasty, more adverse effects such as infection, extrusion, movement, irregularities, absorption, prolonged swelling, seroma, and contracture have been recognized and reported in the literature. Surgeons should be able to recognize these probable complications and manage them successfully. Early detection and prompt management of the complication are essential for minimizing the severity of the deformity. Proper management of complications is key for the success of dorsal augmentation using alloplastic implants.
Keywords: complications; rhinoplasty; alloplast